2023
DOI: 10.1097/ccm.0000000000006093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Standardized Family Participation Program in the ICU: A Multicenter Stepped-Wedge Cluster Randomized Controlled Trial*

Boukje M. Dijkstra,
Paul J.T. Rood,
Steven Teerenstra
et al.

Abstract: Objectives: To determine the effect of a standardized program for family participation in essential care activities in the ICU on symptoms of anxiety, depression, posttraumatic stress and satisfaction among relatives, and perceptions and experiences of ICU healthcare providers (HCPs). Design: Multicenter stepped-wedge cluster randomized controlled trial. Setting: Seven adult ICUs, one university, and six gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A review of family members' role in pain management in the ICU concluded that family members were willing and capable of contributing in pain assessment and management, but research on this topic was scarce 26 . In existing literature, family members' contribution in the ICU is commonly described as either family participation, 27 family involvement, 2,12 or family engagement 28 . For this study, family engagement is considered the proper term to use, as the researchers understand “engagement” as more proactive than “participation” or “involvement.” There is a gap in knowledge about family members' engagement in symptom communication, assessment, and management.…”
mentioning
confidence: 99%
“…A review of family members' role in pain management in the ICU concluded that family members were willing and capable of contributing in pain assessment and management, but research on this topic was scarce 26 . In existing literature, family members' contribution in the ICU is commonly described as either family participation, 27 family involvement, 2,12 or family engagement 28 . For this study, family engagement is considered the proper term to use, as the researchers understand “engagement” as more proactive than “participation” or “involvement.” There is a gap in knowledge about family members' engagement in symptom communication, assessment, and management.…”
mentioning
confidence: 99%